Intrapartum hypoxia and sexual dimorphism in adverse perinatal outcomes. (May 2020) - Mathewlynn, Sam; Knutzen, Liv; Impey, Lawrence
Highlights: Term male babies have worse outcomes although the mechanism remains unclear. It is unknown what role labour may play. Males have more 'fetal distress', have a slightly lower mean cord pH but are not more frequently acidemic. These do not, however, account for their increased incidence of adverse outcomes. Labour is unlikely to be contributory to the 'male disadvantage'. Abstract: Objectives: The aim of this study is to evaluate whether markers of intrapartum hypoxia differ according to sex, and if this could explain the increased risk of adverse perinatal outcomes in males. Study design: This is a retrospective observational cohort study of non-anomalous, singleton deliveries >36 completed weeks' gestation at a UK teaching hospital over a 4.5 year period. Absent or incomplete cord gas results were excluded and the remaining data were validated according to an established method. The relations between sex and both arterial pH and a composite variable, 'fetal distress' (cases in which operative delivery or caesarean section were undertaken for presumed fetal compromise), were examined using independent samples t -test and Chi-square test. Odds ratios with 95 % confidence intervals were calculated to describe the relation between fetal sex and intermediate-term adverse outcomes. Binary logistic regression was performed to generate odds ratios (with 95 % confidence intervals) adjusted for arterial pH and fetal distress. This was repeated to adjust for labor and induction of labor. Results: There were eligible 8758 cases, of which 4655 were male and 4103 female, from a total of 39, 148 deliveries during the study period. Neonatal unit admission (OR 1.54, 95 % CI; 1.31–1.80), renal impairment (OR 1.63, 95 % CI; 1.15–2.32), neurological impairment (OR 1.73, 95 % CI; 1.06–2.84) and a composite adverse outcome (OR 1.73, 95 % CI; 1.29–2.33) were all more likely in males, even after adjusting for labor and induction of labor, both of which were more likely males. The mean cord arterial pH of males was lower (7.23 vs 7.24, P = 0.019) although they were not more likely to be acidemic with a pH <7.0 (males 43 (0.92 %) vs females 41 (1.00 %), P = 0.717), and males were also more likely to have fetal distress (834 (17.9 %) vs 588 (14.3 %), P = <0.001). Being male remained associated with adverse outcomes despite adjustment for arterial pH and fetal distress. Conclusion: Despite a lower mean cord arterial pH and greater incidence of fetal distress in males, intrapartum hypoxia does not account for their worse neonatal outcomes.